THE PROJECT-BASED LEARNING MANAGEMENT ON KWAN PHAYAO STUDIES TO PROMOTE THE PRODUCTIVE CITIZEN SKILLS OF THE STUDENTS AT RAJAPRAJANUGROH SCHOOL 24, PHAYAO PROVINCE - Sunanta, Roongsuriyan; Mangkhang, Charin; Dibyamandala, Jarunee (Journal of Buddhist Anthropology, 2021)
The objectives of this research article were to 1) develop the lesson plans about the project-based learning entitled Kwan Phayao Studies in order to promote productive citizenship skills. 2) study the results of project-based learning management entitled Kwan Phayao Studies. This research is quasi-experimental by employing the form of one-group design with project-based learning. The random samples in this study were 33 students from Mathayomsuksa 3 at Rajaprajanugroh School 24, Phayao Province. The study was carried during semester 2, in the academic year 2018. The research instruments consisted of 1) five lesson plans of a project-based learning. 2) The productive citizenship skill test with open-ended questions. The average ( ) and the standard division (S.D.) were used in this study. The results of this study were as follows; 1) According to the Index of Consistency (IOC) of the project-based learning lesson plans, it revealed that it was 0.87. This implied that the consistency of the lesson plans was qualified to apply with the samples in research. The researchers had also employed the five DePDoRP processes. it found, from the observation of the students’ learning behaviors in each step of the project-based learning, that these were the processes that can support the students’ productive citizenship skills. 2) Regarding the results of the students’ productive citizenship skills, the overall average of the productive citizenship skills was at 3.54 which was of a satisfactory level and the standard deviation (S.D.) was 0.50. Additionally, the students were equipped with the seven productive citizenship skills. According to the results, 57.57 % of the students were in the excellent level of productive citizenship skills as well as 42.43% of them were represented in a good level of productive citizenship skills.